Uncovering the Barriers to Exclusive Breast Feeding for Mothers in a Rural Setting in Southern India - Supriya Venkatachalapathi; Alexander Mannu; Kathir Subramaniyam; Jaishree Vasudevan; Umadevi Lala (Galenos Yayinevi, 2021)
Aim:Exclusive breastfeeding (EBF) is very important for the growth and development of the baby. The purpose of this study was to identify the prevalence of EBF practices, to assess the factors associated with those practices, and to find the barriers to EBF practices in the rural community.Materials and Methods:A cross-sectional study based on systematic questioning was carried out involving 252 mothers with children between the ages of 6 and 9 months in the southern Chennai community and the nearby districts of Chengalpattu and Kanchipuram from October 2018 to October 2019. Multiple logistic regression was used to determine factors associated with EBF.Results:Seventy percent (184/252) of mothers following EBF habits had a child older than six months. About 58% of mothers started breastfeeding within one hour of birth, and 32.53% reported colostrum feeding. An apparent shortage of milk (58.82%) was a common problem reported by the mothers leading to EBF discontinuation. Children of working mothers [Odds ratio (OR) 3.32; 95% confidence interval (CI) 1.13, 9.70], urban dwellers (OR 6.67; 95% CI 1.12, 39.66) and children in urban areas (OR 12.47; 95% CI 2.05, 75.90) were less likely to be breastfed exclusively as indicated in the multivariate regression analysis. No relationships were found between the child's gender, method of childbirth, medical advice, or nutritional management before meals and EBF.Conclusion:Working mothers and those living in urban areas were at greater risk of non-compliance with EBF. The national impact of urban sprawl and the impact on EBF activities should be studied in depth.